Antioxidant property from ziziphus mauritiana / Mohammad Hafiz Sulaiman - Sulaiman, Mohammad Hafiz (2018)
Ziziphus mauritiana or locally known in Malaysia as “Bidara” or “Epal Siam”are categorized as fruit tree species that commonly found in tropical and sub-tropical regions where each parts of Ziziphus mauritiana including its leaves, roots, and fruits have their own unique medicinal use for treatment of multiple kinds of diseases such as allergies and ulcers. This study aims to investigate the antioxidant property in different parts of Ziziphus mauritiana which are the leaves and stems that might be commercialized as sources of natural antioxidant. The total phenolic content (TPC) was determined by the Folin-Ciocalteu method and calibration curve with gallic acid as standard solution was plotted. While for the DPPH radical-scavenging activity of Ziziphus mauritiana was evaluated by using the formula to obtain the percentage of DPPH control. In this study, results showed a higher production of TPC in leaves than stems and higher in methanol than in chloroform. This is in conjunction with DPPH scavenging activity which is higher in leaves than in stems and also recorded higher in methanol than in chloroform.